Efeitos da imersão em água gelada sobre as alterações bioquímicas induzidas pelo exercício físico exaustivo em camundongos - Furtado, Andrezza Bond Vieira (2017)
When exercise is performed intensively or exhaustively, it generates excessive inflammatory response that may lead to muscle damage. Cryotherapy using cold-water immersion is known for its anti-inflammatory and analgesic properties, and it is largely used to accelerate the muscular recovery process. The present study aimed to establish which effects are promoted by continuous cold-water immersion treatment in mice submitted to exercise-induced exhaustion after muscle damage. Swiss albino mice were divided into 4 treatment groups: Control, Cold-water Immersion (CWI), Swimming Exhaustive Protocol (SEP), and SEP+CWI. Treatment groups were subdivided in times of analysis: 0, 1, 3 and 5 days. Exhaustion groups were submitted to one SEP session, and the CWI groups submitted to one CWI session every 24 h (12 minutes at 12°C) every 24 h. Reactive species production, inflammatory and damage biomarkers, cell viability and antioxidant status were assessed. SEP+CWI group showed a decrease in the levels of inflammatory and damage biomarkers and reactive species production, and presented increased cell viability when compared to the SEP group. Additionally, strong correlations between non-protein –SH levels and oxidized dichlorofluorescein, and creatine kinase were found. Furthermore, CWI increased acetylcholinesterase activity in the first two sessions. This study aimed to monitor the evolution of biochemical changes caused by exhaustive exercise and CWI treatment in time. The present study reports that CWI is an effective treatment after exercise-induced muscle damage. It is able to enhance anti-inflammatory response, decrease reactive species production, increase cell viability and promote redox balance, which shorten the recovery process.